Barcelona Lymphedema Algorithm for Surgical Treatment in Breast Cancer–Related Lymphedema - Masià, Jaume; Pons, Gemma; Rodríguez-Bauzà, Elena (Journal of Reconstructive Microsurgery, 2016)
Background Breast cancer–related lymphedema is a prevalent condition that has a major impact on quality of life. Surgical treatment has become an alternative to help affected patients with good results. However, there is no consensus on surgical procedure and protocol.Methods We analyzed our data in two periods: from June 2007 to December 2011 and from January 2012 to June 2014. Data included the analysis of the limb circumferences and the subjective symptoms felt by patients.Results Of the 200 patients treated in the study, 81 had lymphaticovenous anastomosis, 7 had autologous lymph node transfer, 16 had total breast anatomy restoration, 52 had vibroliposuction, and 44 had combined reconstructive procedures. In the first period, the circumference of the superior limb showed a decrease of 0.9 to 6.1 cm (average 2.75 cm). In the second period, the circumference of the superior limb showed a decrease of 2.9 to 6.1 cm (average 3.85 cm). Clinical results and data from the questionnaires confirmed the improvement and subjective benefits.Conclusion We have obtained considerable improvements in results of limb circumferences and subjective symptoms after incorporating several modifications into our surgical strategy for lymphedema treatment. A detailed preoperative assessment should be performed to determine whether reconstructive surgery or palliative surgery is indicated.
Keywords: breast cancer–related lymphedema; lymphedema surgical treatment; Barcelona lymphedema algorithm